BUSINESS ANALYSIS OF PLANT GROWTH-PROMOTING RHIZOBACTERIA (PGPR) PRODUCTION AT CV. BANUA SEJAHTERA LESTARI IN DANAU KARYA VILLAGE, BARITO KUALA REGENCY - Alpiani Alpiani; Ana Zuraida; Fuzi Maulana Ash’ari (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
This study investigates the technical and economic aspects of Plant Growth-Promoting Rhizobacteria (PGPR) production at CV. Banua Sejahtera Lestari in Danau Karya Village. Using a case study approach, the analysis covers production methods, cost structure, profitability, and operational challenges. PGPR production follows strict Standard Operating Procedures (SOP), utilizing laboratory-grade equipment in hygienic conditions under supervision by qualified personnel. Each cycle spans 15 days and is repeated twice monthly, yielding 200 liters per cycle. The production cost per cycle is IDR 2,600,000, while revenue reaches IDR 4,000,000, resulting in a net profit of IDR 1,400,000. The Return Cost Ratio (RCR) of 1.53 indicates economic feasibility and a favorable return on investment. Challenges include maintaining consistent product quality and managing production risks. Overall, PGPR production at CV. Banua Sejahtera Lestari demonstrates strong potential for sustainable agribusiness development in Barito Kuala Regency.